1982
DOI: 10.1007/bf00305554
|View full text |Cite
|
Sign up to set email alerts
|

The human thyrocervical trunk: Configuration and variability reinvestigated

Abstract: Reinvestigation of the configuration of the human thyrocervical trunk revealed, that in the presently investigated specimens the dorsal scapular artery is a direct branch of the subclavian artery in approximately 75% of the cases, whereas in the remaining 25% it is derived from the thyrocervical trunk, either directly or via the transverse cervical artery (Nomina anatomica 1977). The internal thoracic artery participates in the thyrocervical trunk in more than 10% of the observed cases. Thus, both dorsal scapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Very rarely has a situation such as ours been described where the inferior thyroid artery arises from a vertebral artery, which, in turn, is derived from the aortic arch (Adachi, 1928;Sartor et al, 1980). Variations in the pattern of branches originating from the thyrocervical trunk are, however, frequent (Lischka et al, 1982). A thyroidea ima is frequently present (9.6%) (Adachi, 1928).…”
Section: Discussionmentioning
confidence: 98%
“…Very rarely has a situation such as ours been described where the inferior thyroid artery arises from a vertebral artery, which, in turn, is derived from the aortic arch (Adachi, 1928;Sartor et al, 1980). Variations in the pattern of branches originating from the thyrocervical trunk are, however, frequent (Lischka et al, 1982). A thyroidea ima is frequently present (9.6%) (Adachi, 1928).…”
Section: Discussionmentioning
confidence: 98%
“…Two pairs of arteries are involved in the vascularization of the larynx (1,15,16,21,(29)(30)(31)(32)(33) (Figs 4, 5). The superior thyroid artery arises as the first ventral branch of the external carotid artery.…”
Section: Arterial Supply and Gross Innervation Of The Larynxmentioning
confidence: 99%
“…In the majority of individuals studied so far, the inferior thyroid artery was seen to be the main branch of the thyrocervical trunk, which, in turn, originates from the first or thoracic part of the subclavian artery (1,16,21,(29)(30)(31). It first arches upwards, then downwards to reach the inferior border of the lobe of the thyroid gland (16,21).…”
Section: Arterial Supply and Gross Innervation Of The Larynxmentioning
confidence: 99%
“…Moreover, Henriquez-Pino et al found that the right ITA originated as a single trunk from the SCA in 95 % of total cases [16]. Lischka et al (1982) [26] mentioned that in a considerable incidence of 10 % the left ITA originated from the TCT, while the right ITA had the same origin only in 2 %. They also highlighted that in some cases ITA may give off branches usually classified as TCT branches.…”
Section: Discussionmentioning
confidence: 99%